Effect of antipsychotic dose reduction on cognitive function in schizophrenia. (February 2022) - Singh, Animisha; Kumar, Vijay; Pathak, Harsh; Jacob, Arpitha A; Venkatasubramanian, Ganesan; Varambally, Shivarama; Rao, Naren P
Highlights: Treatment of cognitive deficits in schizophrenia is an unmet need. We assessed whether antipsychotic dose reduction will improve cognitive deficits. Decrease in antipsychotic dose was significantly better than continuation of same dose. Dose reduction was not associated with relapse of positive symptoms. Antipsychotic dose reduction may be better than discontinuation. Abstract: Cognitive deficits are predictors of social functioning but remain an unmet therapeutic challenge. While lowering the antipsychotics carries a risk of relapse, it possibly has a beneficial effect on cognitive function. However, this has not been examined in a real-world setting. A prospective naturalistic 6-month follow-up study ( n  = 71) was conducted with patients between 18 and 45 years in their first five years of illness and the maintenance phase of the treatment. Brief Assessment of Cognition in Schizophrenia (BACS) was administered to assess cognitive functions. Patients were divided into three groups based on the change in dose of antipsychotics. The data were analyzed using linear mixed-effects modeling (LMEM) to examine the group differences. At the end of six months, those with decreased antipsychotic dose had significant improvement in BACS total score, token test, and symbol coding compared to those with no change in the dose of antipsychotic. Reducing the dose of antipsychotics during the maintenance phase was associated with improved cognitive functions without an increased risk of relapse. Antipsychotic dose reduction may be better than discontinuation as the relapse risk is higher with the discontinuation strategy. Clinicians must balance the improvements in cognitive functions and relapse risk.